Weighted voting on the IMF Managing Director - Alexander Mayer; Stefan Napel (Economics of Governance, 2020)
Executive Directors of the International Monetary Fund elect the Fund's Managing Director from a shortlist of three candidates; financial quotas of IMF members define the respective numbers of votes. The implied a priori distribution of success (preference satisfaction) is compared across different electoral procedures. The USA's Executive Director can expect to come closer to its top preference under plurality rule than for pairwise majority comparisons or plurality with a runoff; opposite applies to everybody else. Differences of US success between voting rules dominate the within-rule differences between most other Directors, and much of the latest reform of quotas.
Keywords: 330; IMF executive board; IMF quota reform; Weighted voting; Voting procedures; Non-binary voting